Elucidating the clinical, microbiological and molecular diagnostic aspects of Macrophomina phaseolina keratitis. (26th April 2022) - Ahirwar, Lalit Kishore; Sheba, Esther; Jakati, Saumya; Jayasudha, Rajagopalaboopathi; Padakandla, Shalem Raj; Bagga, Bhupesh; Sharma, Savitri
Abstract: This study reports the clinico-microbiological features of Macrophomina phaseolina keratitis. Clinically diagnosed as microbial keratitis, six patients underwent microbiological evaluation. Fungal culture isolates from cornea were subjected to DNA sequencing of the ITS region, phylogenetic analysis and reconfirmation by polymerase chain reaction (PCR). Minimum inhibitory concentrations (MICs) of six antifungal drugs were determined by microbroth dilution method against the six isolates. All patients were treated with antifungals. Failed medical therapy necessitated therapeutic penetrating keratoplasty (TPK). Corneal buttons were processed for histopathology. In all patients, the corneal scraping showed septate hyaline fungal filaments. The BLAST analysis for ITS sequences of all six fungal isolates suggested M. phaseolina, however, when limited to sequences from type material, they matched M. pseudophaseolina . Phylogenetic analysis could not differentiate between these two species and clustered in a single clade. PCR assay of specific gene sequence [ MpCal (calmodulin)] reconfirmed all isolates as M. phaseolina . The MICs of voriconazole and posaconazole were lowest (0.03 to 2 and 0.1 to 2 µg/ml respectively) and all isolates were susceptible to natamycin. Except for case 1, which healed with a scar on treatment, all other cases worsened, despite medical treatment, necessitating TPK. Histopathology of three out of four buttons showed the presence of fungal filaments. While direct microscopic examination of corneal scrapings is helpful in diagnosis, identification of M. phaseolina in culture is challenging. Although MICs of commonly used antifungals are low, response to medical therapy is not encouraging; patients may require TPK for resolution of infection in M. phaseolina keratitis. Lay Summary: DNA sequencing, phylogenetic analysis and specific PCR confirmed Macrophomina phaseolina keratitis in six patients. Although antifungal susceptibility showed the organisms to be susceptible to natamycin five patients did not respond to treatment and needed keratoplasty.